2019
DOI: 10.1103/physrevb.100.115204
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of incoherent exciton formation inCu2O: Time- and angle-resolved photoemission spectroscopy

Abstract: We study dynamics of incoherent exciton formation under interband photoexcitation in Cu 2 O using time-and angle-resolved photoemission spectroscopy at 90 K. Hot electrons injected by allowed optical transitions with 3.40-eV photons show ultrafast relaxation to the conduction-band minimum (CBM), surviving up to 500 fs after excitation. While hot-electron states with high excess energy show a rapid population decay of ~25 fs, an abrupt increase to 130 fs is observed for states with excess energies of 0.15 eV. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Based on the discussion of the excitonic interaction in this material, we naturally check how a direct photoemission feature from excitons looks like. An excitonic feature in photoemission spectra was recently observed and characterized in detail with the pump-and-probe photoemission method as an excited state above the Fermi level and below the bottom of the conduction band 38,[53][54][55] . We adopt this analysis established for pump-excited excitons while we are dealing with a spectroscopic feature below the Fermi level for a spontaneously formed steady-state object.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the discussion of the excitonic interaction in this material, we naturally check how a direct photoemission feature from excitons looks like. An excitonic feature in photoemission spectra was recently observed and characterized in detail with the pump-and-probe photoemission method as an excited state above the Fermi level and below the bottom of the conduction band 38,[53][54][55] . We adopt this analysis established for pump-excited excitons while we are dealing with a spectroscopic feature below the Fermi level for a spontaneously formed steady-state object.…”
mentioning
confidence: 99%
“…Another interesting observation is the significant broadening of the excitonic photoemission peak. The possible contributions for the broadening include (i) the intrinsic scattering of excitons, (ii) the broadening along kz arising from the finite extent of the excitonic wave function in the zdirection 53 and (iii) the finite experimental resolution. Since the experimental resolution is set to ~40 meV and the kz-broadening is also a few tens of meV, limited by the dispersion width in the valence band in the Γ-Υ direction (see Fig.…”
mentioning
confidence: 99%
“…For example, experiments on a topological insulator Bi 2 Se 3 showed that while electrons rapidly disappear from the bulk conduction band, the dynamics of the topological surface state are much slower [18]. More detailed analysis may reveal intricate details of the population dynamics, which has been applied to a wide variety of systems [3,[19][20][21][22][23] A question arose from this work: what do the obtained dynamics (typically decaying exponentials) correspond to? This particular point is where the connection to equilibrium breaks down; the decay rate along t rel , which is related to the equilibrium self-energy via Eq.…”
Section: A Population Dynamicsmentioning
confidence: 99%
“…Several theoretical efforts have begun in this direction, showing that the resulting spectra are a complex mixture of the valence and conduction bands [32][33][34][35][36][37]. Experimentally, in the two-dimensional di-chalcogenide materials, where the exciton binding energy is high, a direct excitation into the exciton yields a clear signature in trARPES [23,[38][39][40][41].…”
Section: Excitonsmentioning
confidence: 99%
“…As the title of this review highlights we want to discuss the role played by coherence in the TR-ARPES phenomenology [146,147,148,149,150,151]. As it was introduced in the Section 2 by using simple arguments, the excitation with an external laser pulse transfers coherence in the system.…”
Section: Coherent and Incoherent Regimes: Preliminary Remarksmentioning
confidence: 99%